A CIPP MODEL-BASED EVALUATION OF ENTREPRENEURSHIP PROJECT BASED LEARNING FOR DEVELOPING STUDENTS'ENTREPRENEURIAL CHARACTER: A CASE STUDY AT SMA NEGERI 3 SEMARANG. - Hidayah, Anisa Nur; Widodo, Joko; Kusumantoro (Journal of Economic Education, 2025)
This study aims to evaluate the implementation of entrepreneurship project based learning in shaping students' entrepreneurial character using the Context, Input, Process, and Product (CIPP) evaluation model at SMA Negeri 3 Semarang. The research employs an evaluation design with a qualitative approach. The primary focus is directed toward assessing the entrepreneurship project learning program implemented at the school. Data were collected through interviews, document analysis, and observation. To ensure data validity, the study applied extended observation, triangulation of sources, methods, and time. Data were analyzed using the processes of data condensation, data display, and drawing conclusions. The findings of the study are categorized into contextual aspects, which include: (1) learning objectives identified as being in very good condition; (2) learning needs categorized as good; and (3) the learning environment assessed to be in very good condition. In terms of input aspects, the evaluation results indicate: (1) the teacher’s role in guiding and facilitating students is in good condition; (2) the teacher’s role in fostering students’ entrepreneurial character is also in good condition; (3) student participation in learning is found to be in poor condition; (4) students' project-related skills are in very good condition; (5) the availability of learning spaces is considered good; and (6) the condition of learning tools is assessed is not good. The process aspect, which pertains to the implementation of entrepreneurship project learning, is generally in good condition. In the product aspect, the evaluation reveals: (1) student learning outcomes are categorized as good; and (2) the entrepreneurial character traits developed through the program include creativity, responsibility, self-confidence, and innovation